Ageing population and economic growth: evidence from Malaysia - Taasim, Shairil Izwan (Sciencedomain International, 2020)
This main purpose of this article investigated the impact of ageing population on economic growth in Malaysia. Annual time series data for 27-year duration (1990-2017) was used and the autoregressive distributed lag (ARDL) was applied. This study will focuses on addressing role of ageing population in Malaysia by context that failed to receive much attention especially in employment sector. By using Romer [1] endogenous theory, the cointegration result revealed that exists a long run relationship exists between ageing population in Malaysia government development expenditure in education and economic growth. Our analysis recommends further investment in government expenditure in education sector to achieving higher human capital capability as a towards high income country and ageing phenomena.